PENGARUH PENERAPAN SALURAN DISTRIBUSI TERHADAP TINGKAT PENDAPATAN PADA PENGUSAHA KRIPIK PISANG DIKOTA METRO TAHUN 2016 - Tri Aryanti Tri Aryanti; Maryatun Maryatun (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
Marketing is an essential activity in the company. Marketing is a system in the whole of the business activities shown to plan, price, promote, and distribute goods and services that satisfy the needs, both of the existing buyers and the potential buyers. The purpose of this research is: